Lidocaine/ketorolac-loaded biodegradable nanofibrous anti-adhesive membranes that offer sustained pain relief for surgical wounds - Kao CW (Dove Medical Press, 2017)
Ching-Wei Kao,1,2 Demei Lee,2 Min-Hsuan Wu,2 Jan-Kan Chen,3 Hong-Lin He,4 Shih-Jung Liu2,5 1Department of Anesthesiology, Chiayi Chang Gung Memorial Hospital, Chiayi, 2Department of Mechanical Engineering, 3Department of Physiology and Pharmacology, Chang Gung University, Taoyuan, 4Department of Pathology, E-DA Hospital, I-Shou University, Kaohsiung, 5Department of Orthopedic Surgery, Chang Gung Memorial Hospital, Taoyuan, Taiwan Abstract: The aim of this study was to develop and evaluate the effectiveness of biodegradable nanofibrous lidocaine/ketorolac-loaded anti-adhesion membranes to sustainably release analgesics on abdominal surgical wounds. The analgesic-eluting membranes with two polymer-to-drug ratios (6:1 and 4:1) were produced via an electrospinning technique. A high-performance liquid chromatography (HPLC) assay was employed to characterize the in vivo and in vitro release behaviors of the pharmaceuticals from the membranes. It was found that all biodegradable anti-adhesion nanofibers released effective concentrations of lidocaine and ketorolac for over 20 days post surgery. In addition, a transverse laparotomy was setup in a rat model for an in vivo assessment of activity of postoperative recovery. No tissue adhesion was observed at 2 weeks post surgery, demonstrating the potential anti-adhesion capability of the drug-eluting nanofibrous membrane. The postoperative activities were recorded for two groups of rats as follows: rats that did not have any membrane implanted (group A) and rats that had the analgesic-eluting membrane implanted (group B). Rats in group B exhibited faster recovery times than those in group A with regard to postoperative activities, confirming the pain relief effectiveness of the lidocaine- and ketorolac-loaded nanofibrous membranes. The experimental results suggested that the anti-adhesion nanofibrous membranes with sustainable elution of lidocaine and ketorolac are adequately effective and durable for the purposes of postoperative pain relief in rats. Keywords: biodegradable nanofiber, anti-adhesive membrane, sustainable release, lidocaine, ketorolac